SEMIOTIC ANALYSIS OF THE POLITICAL COMMUNICATION PATTERNS OF JOKO WIDODO AND NAHDLATUL ULAMA IN THE 2019 PRESIDENTIAL ELECTION CAMPAIGN - Achmad Nafhis Ubaydillah; Effy ZalfianaRusfian (Bajang Institute, 2021)
Semiotics is used as the basis for the meaning contained in each message, especially regarding political communication which uses a reference that every message meaning is contained in it. A political communication that uses the interactional communication model carried out by Joko Widodo and Nahdlatul Ulama convinces the public to support Joko Widodo as a candidate for President of Indonesia in 2019. Semiotics has a relationship with the prevailing culture in an area due to signs and patterns of political communication. carried out by Joko Widodo and Nahdlatul Ulama is believed to be a communication process and uses signs and figures of speech through the metaphor of political communication by referring to the communication made between the two actors to participate in seeing the communication process by sending messages to the public. Semiotics is used in a message as well as to be sent to the public. The campaign carried out by Joko Widodo has a close relationship with Nahdlatul Ulama as the two of them did to believe in all Indonesian people with the messages sent by both of them. However, the semiotic element contained in the political communication carried out by Joko Widodo and Nahdlatul Ulama invites the Indonesian people to follow what is done by interpreting the meaning of semiotics in the political messages sent by Joko Widodo and Nahdlatul Ulama to the Indonesian people.